2018
DOI: 10.1002/oby.22110
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Curcumin Intervention Targets Mouse White Adipose Tissue Inflammation and Brown Adipose Tissue UCP1 Expression

Abstract: Curcumin intervention targets both WAT inflammation and BAT UCP1 expression. These observations advanced our knowledge on the metabolic beneficial effects of the curry compound curcumin, bringing us a novel perspective on dietary polyphenol research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 45 publications
1
46
0
1
Order By: Relevance
“…Primary adipocytes treated with curcumin have increased UCP1, PPARα and PGC-1α mRNA levels. Curcumin treatment increased UCP1, PPARα, PPARγ and PGC-1α mRNA levels in mBACs (Table 1) [69].…”
Section: Effects Of Curcumin: In Vitro Adipocyte Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary adipocytes treated with curcumin have increased UCP1, PPARα and PGC-1α mRNA levels. Curcumin treatment increased UCP1, PPARα, PPARγ and PGC-1α mRNA levels in mBACs (Table 1) [69].…”
Section: Effects Of Curcumin: In Vitro Adipocyte Studiesmentioning
confidence: 99%
“…Treatment of primary adipocytes and mouse brown adipocyte cells (mBACs) with curcumin (2 µM) for 10 h resulted in improved thermogenesis [69]. Primary adipocytes treated with curcumin have increased UCP1, PPARα and PGC-1α mRNA levels.…”
Section: Effects Of Curcumin: In Vitro Adipocyte Studiesmentioning
confidence: 99%
“…Specifically, Curcumin intervention was found to reduce mouse WAT inflammation and increase BAT UCP1 expression via PPAR-dependent and -independent mechanisms. It reduces macrophage infiltration and proinflammation cytokine expression in both macrophages and adipocytes along with increased energy expenditure and body temperature in response to cold (209).…”
Section: Anti-inflammatory Pathways and Bat Functionmentioning
confidence: 99%
“…Importantly, ω3-FAs (n-3 polyunsaturated fatty acids (n-3PUFAs) have anti-inflammatory effects and may significantly impact chronic inflammatory diseases including obesity related disorders (210). An ω3enriched diet, in non-obesogenic non-inflammatory conditions, leads to synthesis of oxylipins which have an anti-inflammatory response in both WAT and BAT with a macrophage modulation effect, but with no influence on inflammatory cytokine secretion (209). FFAs are active stimulators for members of the rhodopsinlike family of G protein-coupled receptors (GPCRs) including GPR40, GPR41, GPR43, GPR84, and GPR120 (211,212).…”
Section: Anti-inflammatory Pathways and Bat Functionmentioning
confidence: 99%
“…Recently, Wang et al showed that a dietary CUR supplement improved insulin sensitivity and decreased body fat in mice with high-fat diet (HFD)-induced obesity [19] and obese/diabetic mice [20]. A dietary CUR supplement has been shown to relieve low-grade chronic WAT in ammation and upregulate BAT UCP1 expression in HFD mice [21]. In addition, CUR has been reported to be an anti-adipocyte dietary bioactive component largely involved in modulating the early stage of adipocyte differentiation [22].…”
Section: Introductionmentioning
confidence: 99%